Welcoming gender diversity in the early years: Interpreting professional guiding documents for gender-expansive practice. (March 2023) - Timmons, Kristy; Airton, Lee
This research takes up the challenge of interpreting the two newest grounds of human rights protection across Canada – gender identity and gender expression – for professional practice in early childhood education. To date, no human rights tribunal ruling on these grounds has engaged early childhood education, and while the legal duty remains for early childhood educators to provide an environment free of gender-identity and gender-expression discrimination, the Ontario profession's governing bodies have provided no explicit guidance as to how. This research bridges early years educators' new and likely unfamiliar legal responsibilities in relation to both grounds and everyday life in early years contexts. The findings demonstrate that ample support exists within the profession's key guiding documents for 'gender-expansive' practice, or an approach to teaching children and supporting their development that both expects and sustains gender diversity. A similar analysis of guiding documents is needed internationally.